Injury-related childhood mortality in migrant households in a southern city of China. Issue 3 (22nd June 2010) - Wang, H; Smith, G A; Stallones, L; Xiang, H
Abstract : Background: Sporadic evidence from China suggests that migrant children are at higher risk of injury-related mortality than local indigenous children. Methods: Child deaths from 2004 to 2008 were provided by the Shenzhen Women and Child Health Surveillance System. Population data for children 1–4 years old were obtained from the Shenzhen Bureau of Statistics and number of live births was obtained from birth registration records. All-cause and injury-related childhood mortality rates and death causes were calculated and compared. Results: A total of 3774 deaths were identified. All-cause mortality rates per 10 000 dropped significantly from 66.28 (95% CI 60.50 to 72.06) in infants (<1 year old) and 7.40 (95% CI 6.16 to 8.64) in early childhood (1–4 years old) in 2004 to 40.42 (95% CI 37.31 to 43.53) and 3.97 (95% CI 3.36 to 4.58) in 2008. However, injury-related mortality rates did not change significantly from 2.36 (95% CI 1.27 to 3.45) in infants and 2.97 (95% CI 2.19 to 3.76) in early childhood in 2004 to 2.00 (95% CI 1.31 to 2.69) and 2.00 (95% CI 1.56 to 2.43) in 2008. Injury-related mortality rates were significantly higher among migrant children (p<0.05). Drowning and traffic crashes were the top two causes of early childhood injury deaths; suffocation was the leading cause of infant injury deaths. Conclusion: Migrant children were at significantly higher risk of injury-related mortality than local indigenous children. Injury prevention in Shenzhen should target drowning and traffic safety among young children and suffocation among infants as top priorities.